2011
DOI: 10.1292/jvms.10-0339
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes, Antimicrobial Susceptibility, and Minimal Inhibitory Concentrations of Actionbacillus pleuropneumoniae Isolated from Slaughter Pigs in Taiwan (2002-2007)

Abstract: ABSTRACT. In total, 211 isolates of A. pleuropneumoniae were collected from pigs with hemorrhagic pneumonia at slaughterhouses during [2002][2003][2004][2005][2006][2007]. Serotypes, antimicrobial susceptibility and minimum inhibitory concentration (MIC) values were determined for each isolate of A. pleuropneumoniae to 10 antimicrobial agents. Serovar 1 of A. pleuropneumoniae was predominant in Taiwan in 138 of the 211 isolates, followed by serovars 2 and 5. More than 90% of collected isolates were sensitive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
(21 reference statements)
1
8
1
Order By: Relevance
“…Similar results were obtained in other studies for florfenicol (14,32), ceftiofur/cefotaxime (19) and enrofloxacin (24). A high susceptibility to lincospectin correlates with the observed susceptibility of 95% in neighboring Croatia (15), but differs from the results obtained in Taiwan where only 2.4% of the 211 investigated strains were susceptible to this antibiotic (31). High rates of susceptibility of 91% were observed for ampicillin and amoxicillin, which is in agreement with the reports by Matter and Kucerova (19,22).…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results were obtained in other studies for florfenicol (14,32), ceftiofur/cefotaxime (19) and enrofloxacin (24). A high susceptibility to lincospectin correlates with the observed susceptibility of 95% in neighboring Croatia (15), but differs from the results obtained in Taiwan where only 2.4% of the 211 investigated strains were susceptible to this antibiotic (31). High rates of susceptibility of 91% were observed for ampicillin and amoxicillin, which is in agreement with the reports by Matter and Kucerova (19,22).…”
Section: Methodssupporting
confidence: 86%
“…On the other hand, these results differ from the results of Vanni (30) who found 69% and 82% resistance to ampicillin and amoxicillin, respectively. The susceptibility to gentamicin in our study was 77%, which is much higher than susceptibil- ity rates of 5.7% and 43% published by other authors (26,31). In our study the highest resistance rates were determined to tetracycline (34%) and streptomycin (31%).…”
Section: Methodscontrasting
confidence: 67%
“…A wide variety of antimicrobial agents have been suggested for treating this disease including b-lactams (amoxicillin, penicillin, ampicillin, and ceftiofur), tetracyclines (tetracycline and doxycycline), florfenicol, trimethoprim/sulfamethoxazole, tiamulin, lincomycin/spectinomycin, fluoroquinolones (danofloxacin and enrofloxacin), and gentamicin. 49 Various antimicrobial resistance patterns have been observed in several studies among strains from different geographical regions, 10,17,23,32 serovars, 3,53,54 and also over time. 22,37,48 While most isolates are reported to be susceptible toward fluoroquinolones, ceftiofur, and florfenicol, resistances toward ampicillin, tetracycline, and other antimicrobials are emerging (reviewed by Aarestrup et al 1 ).…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies reported similar susceptibility data for A. pleuropneumoniae for florfenicol 22,34,54 and ceftiofur. 2,10,31,34,42,44,53,54 However, a recent study from Czech Republic reported for the first time florfenicol resistance at a low degree (0.8%). 32 The presence of the floR gene was detected by PCR in all their resistant isolates.…”
mentioning
confidence: 99%
“…In Taiwan, serovar 1 is the most common serovar isolated, accounting for 65·4% of cases, followed by serovars 2 and 5, with 34·6% (Yang et al . ). As a comparison, in Japan, serovars 2 and 5 are the most commonly isolated, and in Canada, serovars 5 and 7 (Morioka et al .…”
Section: Introductionmentioning
confidence: 97%